Using radiobiology simulators for evaluation of 99mTc Auger electrons for targeted tumor radiotherapy - Adriana Alexandre S. Tavares (2010)
Technetium-99m (99mTc) has been widely used as an imaging agent; however, few studies evaluated its potential use as therapeutic agent. The present study aimed to analyze the potential use of 99mTc Auger electrons for targeted tumor radiotherapy by computational methods. Thus, three different computational simulators were used to estimate the yield of DNA damage, the probability of correct repair and cell kinetic effects after irradiation with 99mTc electrons, iodine-131 beta minus particles and astatine-211 alpha par-ticles. Based on the obtained results, it is possible to conclude that 99mTc CKMMX (all M-shell Coster-Kroning CK and super CK transitions) electrons and Auger MXY (all M-shell Auger transitions) are valuable for targeted tumor radiotherapy.